The Illusion of Attitude Change - Nuttin, Jef (Studia Psychologica, 1996)
In the present monograph some thirteen unpublished experiments are reported which represent the core of a long term research project on attitude change undertaken by the author in close collaboration with Dr. Annie Beckers at the Laboratorium voor Experimentele Sociale Psychologie of the University of Leuven. The starting point of this programme has to be situated in Leon Festinger's 1957 book in which a challenging theory on cognitive integration and change is offered as a common conceptual framework for the understanding of an impressive amount and wide variety of psychological phenomena. The four main classes of research problems which were covered in the original publication are: the consequences of decisions, the effects of forced compliance, the voluntary and involuntary exposure to information and the role of social support.